Stress corrosion cracking of U tube heat exchanger used for low pressure steam generation in a hydrogen unit of petroleum refinery. (July 2022) - Subramanian, Chidambaram; Ghosh, Debashis; Reddy, Dasari Sukumar; Ghosh, Debasmita; Natarajan, Rampradesh; Velavan, SP.
Highlights: Heat exchanger tubes in hydrogen plant of an oil refinery were failed after four years of useful service after replacement. Tubes within tubesheet were considered as critical due to crevice location. Tubes were cold expanded to establish tube to tube sheet joint prior to start of service and shell side deposits were accumulated in crevice location during its service period. Fracture initiated from outer surface of the exchanger tube and failed by chloride stress corrosion cracking with dominant transgranular mode of cracking. Good engineering practices are suggested to mitigate HX failures in oil and gas industries. Abstract: The reformer effluent is serially cooled down to produce hydrogen in the hydrogen unit of an oil refinery. The process heat from effluent is effectively utilized for low pressure steam generation using heat exchanger. The exchanger shell and tube side fluids were boiler feed water and process gas, respectively. Several tubes of this heat exchanger were failed especially within tube sheet after 4 years of useful service. Therefore, failed exchanger tube was subjected to engineering failure analysis to determine the cause of failure. Initially visual inspection was conducted using videoscopy in heat exchanger dry condition and evidenced circumferential crack. Subsequently, all failed tubes were separated from U tube bundle. Selected tube was subjected to visual inspection, dye penetrant and dimensional measurement. No evidence of visual deformation and thickness loss observed in the failed tube. Further investigated tube was subjected to chemical analysis and confirmed the required metallurgy as per design specification. The fracture surface was subjected to elemental analysis, fractographic, metallographic and hardness investigations. The micro hardness of an exchanger tube at failure location was higher than specified hardness value. Investigation also revealed that exchanger tubes were expanded from tube inner surface to establish tube to tube sheet joint according to specified design drawing. Tube expansion was done prior to start of service and attributed to residual stress within tube material. The results revealed that presence of chloride in the accumulated deposits within tube to tube sheet joint favored conducive environment for chloride stress corrosion cracking. Recommendations were suggested for failure prevention. Achievement in this paper may supplement the similar heat exchanger tube failure database and mitigation of failure will be possible by good engineering practices.